# What is the equation of the line tangent to # f(x)=-(x-3)^2-5x-3# at # x=5#?

Equation of tangent is

graph{(9x+y-13)(y+(x-3)^2+5x+3)=0 [-10, 10.8, -60, 20]}

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the line tangent to f(x)=-(x-3)^2-5x-3 at x=5 is y = -4x + 14.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the equation of a line tangent to the function #y=ln(-x)# at (-2,ln2)?
- What is the equation of the line normal to # f(x)=ln(x+xe^(3x))# at # x=2#?
- What is the equation of the line normal to # f(x)=1/(e^x+4)# at # x=6#?
- How do you find the equation of the tangent to the curve #y=x^2+2x-5# that is parallel to the line #y=4x-1#?
- How do you find the average rate of change of the function #f(x)=4 ·x^2 + 2 ·x−4# over the interval [3, 3.17]?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7